Radiation-Induced Immunity and Toxicities: The Versatility of the cGAS-STING Pathway - Constanzo, Julie; Faget, Julien; Ursino, Chiara; Badie, Christophe; Pouget, Jean-Pierre (Frontiers in Immunology, 2021)
In the past decade, radiation therapy (RT) entered the era of personalized medicine, following the striking improvements in radiation delivery and treatment planning optimization, and in the understanding of the cancer response, including the immunological response. The next challenge is to identify the optimal radiation regimen(s) to induce a clinically relevant anti-tumor immunity response. Organs at risks and the tumor microenvironment (e.g. endothelial cells, macrophages and fibroblasts) often limit the radiation regimen effects due to adverse toxicities. Here, we reviewed how RT can modulate the immune response involved in the tumor control and side effects associated with inflammatory processes. Moreover, we discussed the versatile roles of tumor microenvironment components during RT, how the innate immune sensing of RT-induced genotoxicity, through the cGAS-STING pathway, might link the anti-tumor immune response, radiation-induced necrosis and radiation-induced fibrosis, and how a better understanding of the switch between favorable and deleterious events might help to define innovative approaches to increase RT benefits in patients with cancer.